Carbon, Nitrogen, and Phosphorus Stoichiometry and Plant Growth Strategy as Related to Land-Use in Hangzhou Bay Coastal Wetland, China - Xiong, Jing; Shao, Xuexin; Yuan, Haijing; Liu, Enjun; Wu, Ming (Frontiers in Plant Science, 2022)
Ecological stoichiometry can instruct soil nutrient stocks and availability and plant growth strategy and adaptability to environmental changes and stress. This study investigated the correlation between C, N, and P contents and ratios of plant organs and soil depths in different land-use types (mudflat, native wetland, reclaimed wetland, and invasive wetland) in the southern Hangzhou Bay coastal wetland. The results showed that the distributions and patterns of C and N contents among plant organs and soil depths depend on land-use types, while P content had strong stability. Among tidal wetlands, plant N content and C:P, N:P ratios were significantly higher in native wetland than in invasive wetland. In contrast, plant C, N, and P contents and C:P and N:P ratios were significantly lower in reclaimed wetland, and plant C:N was higher. Cs, Ns, and Ps were similar between tidal wetlands, and were significant higher than those of reclaimed wetland, indicating that reclamation were not conducive to soil nutrient storage. In the native wetland, soil N availability was relatively high, and P availability was relatively low; and leaf N:P was 15.33, which means vegetation was co-limited by N and P nutrients. In addition, plants in the native wetland mainly adopted a conservative growth strategy, with a significantly low aboveground biomass of 1469.35 g·m2. In the reclaimed wetland, soil N availability was relatively low, P availability was relatively high, and leaf N:P was 3, which means vegetation was limited by N nutrient. In addition, plants in the reclaimed wetland mainly adopted a rapid growth strategy, with a significantly high aboveground biomass of 3261.70 g·m2. In the invasive wetland, soil N availability was relatively low, soil P availability was relatively high, and leaf N:P was 5.13, which means vegetation was limited by N nutrient. The growth strategy and aboveground biomass (2293.67 g·m2) of the invasive wetland were between those of the native and reclaimed wetlands. Our results provide a reference for managing wetlands and evaluating the impacts of land use types on coastal wetland ecosystems.